The Role of Islamic Religious Education in the National Education System : Kurikulum - Samia Novera; Alfi Lutfiyah; Fauzan; Hanifah Safitri (Jurnal Ilmu Pendidikan dan Sains Islam Interdisipliner, 2026)
Islamic Religious Education (IRE) is a key component of Indonesia’s national education system, serving not only as a means of transmitting religious knowledge but also as an instrument for shaping students’ character and moral values. This article aims to analyze the role of PAI in the national education system amidst the challenges of globalization, digitalization, and rapid social change. The research method employed is qualitative, utilizing a literature review approach (library research), by examining various recent scientific literature indexed in SINTA and other academic sources. The results of the study indicate that PAI continues to hold a strategic position in building national character, despite facing various challenges such as the dominance of cognitive approaches, low levels of technology integration, and issues of intolerance. Therefore, a reconstruction of the PAI paradigm is needed one that is more integrative, contextual, and adaptive to the times to ensure its continued relevance in national education. Keywords: Islamic Religious Education, National Education, Character, Religious Moderation, Digitalization